Frequency effects and the study of Limon’s Spanish copulas: ser and estar - Aguilar-Sánchez, Jorge (2021)
This paper presents a brief but comprehensive review of what has been done regarding the Spanish copula. It explores how frequency effects can help account for the unexplained variance found in the different proposed models, based on the Exemplar Model. This is done to propose a theoretical framework for the study of the Spanish copula in contact situations that include frequency as a variable to understand whether change is ongoing or stable, and whether the change of estar is extending to the contexts of ser, ser is extending to the contexts of estar,  or both phenomena is taking place. I explore how each of the schema components interacts with each other, how these interactions fit into the traditional description of copula choice, and move away from the generative view of language as a set of rules to begin looking at it as a system highly affected by the frequency of use of its components.  I then propose a procedure on how to explain copula behavior in Spanish that includes a multi-level analysis of this phenomenon.